Economics, business and the personalist philosophy - Hoevel, Carlos (2011)
Fil: Hoevel, Carlos. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Departamento de Investigación Francisco Valsecchi; Argentina